Prevalence and associated factors of social phobia among high school adolescents in Northwest Ethiopia, 2021 - Nakie, Girum; Melkam, Mamaru; Desalegn, Getachew Tesfaw; Zeleke, Tadele Amare (Frontiers in Psychiatry, 2022)
Abstract Background: Social phobia is the third most common mental illness in the world. It has a negative impact on educational achievement by increasing school absentees, prevents students to participate in class, and this leads to a significant impairment to emotional, psychological, social, and physical wellbeing of students. Researches done regarding social phobia and associated factors among high school students in low and middle income countries are limited. Therefore the aim of this study is to assess the prevalence and associated factors of social phobia among adolescents have pivotal role for further investigation. Objectives: To assess the prevalence and associated factors of social phobia among high school adolescents in, Northwest Ethiopia, 2021. Methods: An institutional based cross-sectional study was conducted from April 15 to May 14 2021, by using simple random sampling technique to select a sample of 936 participants after proportional allocation to the six high schools. Social phobia was assessed by using social phobia inventory (SPIN), independent variables like social support was assessed by Oslo social support scale, substance related factors by ASSIST, and the rest of other factors were assessed by structured questionnaires’. Binary and multivariate analysis was done to identify factors associated with social phobia. Statistical significant was declared at 95% confidence interval (CI) of p-value less than or equal to 0.05. Result: Prevalence of social phobia among adolescents was found to be 40.2% with (95% CI 37.0 to 43.4%). In the multivariable analysis, female sex (AOR = 1.374, 95% CI 1.016, 1.858), poor social support (AOR=2.408, 95% CI 1.660, 3.493), having known chronic medical illness (AOR=2.131, 95% CI 1.173, 3.870), having history of mental illness in the family (AOR= 1.723 95% CI 1.071, 2.773), and being highly risky alcohol user (AOR=1.992 95% CI 1.034, 3.838) were factors significantly associated with social phobia symptoms. Conclusion: The overall prevalence of SP among adolescents was high. Therefore early detection and adequate intervention is crucial to reduce overall burden of social phobia among adolescents. Keywords: Prevalence, Social phobia, Adolescents, Ethiopia